A phase II randomized clinical trial to assess toxicity and quality of life of breast cancer patients with hypofractionated versus conventional fractionation radiotherapy with regional nodal irradiation in the context of COVID-19 crisis - Gil, Gabriel Oliveira Bernardes; de Andrade, Warne Pedro; Diniz, Paulo Henrique Costa; Cantidio, Farley Soares; Queiroz, Izabella Nobre; Gil, Maria Luísa Braga Vieira; Almeida, Conceição Aparecida Medeiros; Caldeira, Paola Palmer Reis; Regalin, Marcos; Silva-Filho, Agnaldo Lopes (Frontiers in Oncology, 2023)
Purpose This study, conducted during the COVID-19 crisis, primarily aimed to compare the acute toxicity between conventional fractionated radiation therapy (CF-RT) with hypofractionated radiation therapy (HF-RT) among patients who underwent breast-conserving surgery or mastectomy in whom breast or chest wall and regional nodal irradiation (RNI) were indicated. The secondary endpoints were both acute and subacute toxicity, cosmesis, quality of life, and lymphedema features. Methods In this open and non-inferiority randomized trial, patients (n = 86) were randomly allocated 2:1 in the CF-RT arm (n = 33; 50 Gy/25 fractions ± sequential boost [10 Gy/5 fractions]) versus the HF-RT arm (n = 53; 40 Gy/15 fractions ± concomitant boost [8 Gy/15 fractions]). Toxic effects and cosmesis evaluation used the Common Terminology Criteria for Adverse Events, version 4.03 (CTCAE) and the Harvard/National Surgical Adjuvant Breast and Bowel Project (NSABP)/Radiation Therapy Oncology Group (RTOG) scale. For the patient-reported quality of life (QoL), the European Organisation for Research and Treatment of Cancer quality of life questionnaire (EORTC QLQ-C30) and the breast cancer-specific supplementary questionnaire (QLQ-BR23) were used. Lymphedema was assessed by comparing volume differences between the affected and contralateral arms using the Casley–Smith formula. Results Grade 2 and grade 3 dermatitis were lower with HF-RT than with CF-RT (28% vs. 52%, and 0% vs. 6%, respectively; p = 0.022). HF-RT had a lower rate of grade 2 hyperpigmentation (23% vs. 55%; p = 0.005), compared to CF-RT. No other differences in overall rates of physician-assessed grade 2 or higher and grade 3 or higher acute toxicity between HF-RT and CF-RT were registered. There was no statistical difference between groups regarding cosmesis, lymphedema rate (13% vs. 12% HF-RT vs. CF-RT; p = 1.000), and functional and symptom scales, during both the irradiation period and after 6 months of the end of treatment. The results revealed that the subset of patients up to 65 years or older did not show a statistical difference between both arm fractionation schedules (p > 0.05) regarding skin rash, fibrosis, and lymphedema. Conclusion HF-RT was non-inferior to CF-RT, and moderate hypofractionation showed lower rates of acute toxicity, with no changes in quality-of-life outcomes. Clinical trial registration ClinicalTrials.gov, identifier NCT 40155531.